Diagnóstico diferencial das anemias microcíticas e hipocrômicas - Naoum, Paulo Cesar [UNESP] (2011)
The microcytic and hypochromic anemia are the results of several pathologic conditions. They are the most prevalent forms of anemia in the Brazilian population , and frequently the clinical diagnosis depends on the laboratorial analysis. In many cases it is necessary to use specific techniques to determine if this anemia is due to iron deficiency or different types of thalassemia. This article shows the main technical applications used for differential diagnosis of microcytic and hypochromic anemia.